2 - ‘If it ain’t broke, don’t fix it’: Challenges facing institutional transformation of historically white South African universities - Masixole Booi; Louise Vincent; Sabrina Liccardo (African Sociological Review, 2017)
Research on transformation of higher education institutions shows that the underrepresentation, recruitment and retention of blacks and women in senior posts is still the major challenge facing the project of transforming higher education, particularly in Historically White Universities (HWUs). Several South African universities have responded to this challenge by initiating programmes for the ‘accelerated development’ of black academic staff. In this project we were interested to examine the wider implications of such programmes for transforming/reproducing existing institutional cultures. Focusing on one particular HWU and the participants in its Accelerated Development Programme (ADP) we asked whether or not the programme could be thought to have contributed to the interruption or reproduction of the existing dominant institutional culture of the university. The paper is based on interviews with 18 black lecturers who entered the academic workforce through the university’s ADP. Employing Pierre Bourdieu’s theoretical framework of social and cultural reproduction, we discuss how difficult it is to interrupt the naturalised norms and values that form part of the existing institutional culture of a university.